Implementation of Midtrans Payment Gateway in the 81 Coffee Sales Application - Ari anto; Rafie Rafie (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
81 Coffee is a coffee shop business established in Banjarmasin City that faces challenges in its conventional sales system and dependency on third-party marketplaces, which affect profit margins and operational efficiency. This study aims to design and implement a mobile-based coffee sales application to improve transaction efficiency, expand customer reach, and provide a better user experience. The research employed a software development method using the Flutter framework for mobile application development, Firebase as the cloud database, and Midtrans as the payment gateway. The system was tested through functional, integration, and field testing using various devices and network conditions to measure response time, transaction success rate, and data consistency. The results show that the application performs effectively, achieving an average UI response time of 1.2 seconds, payment success rate of 98%, and data consistency of 100%. The integration of Midtrans enables a secure and seamless digital payment process. Overall, the developed system improves operational efficiency and provides a reliable digital sales platform for 81 Coffee’s business operations.